An antidamping spin–orbit torque originating from the Berry curvature - Kurebayashi, H.; Sinova, Jairo; Fang, D.; Irvine, A.C.; Skinner, T. D.; Wunderlich, J.; Novák, V.; Campion, R.P.; Gallagher, B.L.; Vehstedt, E.K.; Zârbo, L.P.; Výborný, K.; et al. (2014)
Magnetization switching at the interface between ferromagnetic and paramagnetic metals, controlled by current-induced torques, could be exploited in magnetic memory technologies. Compelling questions arise regarding the role played in the switching by the spin Hall effect in the paramagnet and by the spin–orbit torque originating from the broken inversion symmetry at the interface. Of particular importance are the antidamping components of these current-induced torques acting against the equilibrium-restoring Gilbert damping of the magnetization dynamics. Here, we report the observation of an antidamping spin–orbit torque that stems from the Berry curvature, in analogy to the origin of the intrinsic spin Hall effect. We chose the ferromagnetic semiconductor (Ga,Mn)As as a material system because its crystal inversion asymmetry allows us to measure bare ferromagnetic films, rather than ferromagnetic paramagnetic heterostructures,eliminating by design any spin Hall effect contribution. We provide an intuitive picture of the Berry curvature origin of this antidamping spin–orbit torque as well as its microscopic modelling. We expect the Berry curvature spin–orbit torque to be of comparable strength to the spin-Hall effect-driven antidamping torque in ferromagnets interfaced with paramagnets with strong intrinsic spin Hall effect.